2007
DOI: 10.2174/156802607782341028
|View full text |Cite
|
Sign up to set email alerts
|

NPY Y1 and Y5 Receptor Selective Antagonists as Anti-Obesity Drugs

Abstract: A combination of pharmacological and genetic studies in mice confirmed that the Y1 and Y5 receptors mediate the potent orexigenic actions of exogenous NPY. Although the physiological role of NPY in causing obesity is less clear, potent and selective antagonists of both Y1 and Y5 have been developed. Some of the NPY antagonists have suitable pharmacokinetic (PK) properties that allowed them to be evaluated in various rodent models of obesity. Several different Y1 and Y5 antagonists cause weight loss in rodent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 124 publications
0
25
0
Order By: Relevance
“…The Y2 and Y4 receptor subtypes are proposed to inhibit appetite, while the Y1 and Y5 subtypes have been implicated in stimulating appetite. Therefore, inhibition of NPY Y1 or NPY Y5 has been pursued as a potential therapy for obesity (MacNeil, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The Y2 and Y4 receptor subtypes are proposed to inhibit appetite, while the Y1 and Y5 subtypes have been implicated in stimulating appetite. Therefore, inhibition of NPY Y1 or NPY Y5 has been pursued as a potential therapy for obesity (MacNeil, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that leptin could stimulate the NPY neuron activity in the hypothalamus in diet-induced obese mice, indicating the role of NPY in leptin-mediated appetite control [63]. Several Y receptor antagonists targeting Y1, Y2, Y4 and Y5 were shown to cause weight loss or protection against diet-induced obesity in rodent models [64,65]. Furthermore, ablation of both Y2 and Y4 receptors in ob/ob mice attenuated the hyperphagia-caused obesity [66].…”
Section: Y Receptorsmentioning
confidence: 99%
“…However, the magnitude of induced-weight loss by MK-0557 (spiro[cyclohexane-1,3′(1′H)-furo[3,4-c]pyridine]-4-carboxamide,N-[1-(2-fluorophenyl)-1H-pyrazol-3-yl]-1′-oxo-, trans-), one of these selective Y 5 antagonists, was not clinically meaningful despite demonstrated high levels of Y 5 receptor occupancy (Erondu et al 2006). Potent and selective antagonists of the Y 1 receptor from various chemical classes have also been developed for the treatment of obesity (MacNeil 2007). In contrast to Y 1 and Y 5 receptor subtypes, for which many selective antagonists from various chemical classes are available, discovering Y 2 receptor antagonists has proven challenging.…”
Section: Introductionmentioning
confidence: 99%